2019
DOI: 10.2967/jnumed.119.233031
|View full text |Cite
|
Sign up to set email alerts
|

Cholecystokinin 2 Receptor Agonist 177Lu-PP-F11N for Radionuclide Therapy of Medullary Thyroid Carcinoma: Results of the Lumed Phase 0a Study

Abstract: Treatment of patients with advanced medullary thyroid carcinoma (MTC) is still a challenge. For more than 2 decades it is known that cholecystokinine-2 receptor (CCK2R) is a promising target for the treatment of MTC with radiolabeled minigastrin analogues. Unfortunately, kidney toxicity precluded their therapeutic application so far. In 6 consecutive patients we evaluated with advanced 3D dosimetry whether improved minigastrin analogue 177 Lu-DOTA-(DGlu) 6-Ala-Tyr-Gly-Trp-Nle-Asp-PheNH 2 (177 Lu-PP-F11N) is a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
64
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 67 publications
(74 citation statements)
references
References 21 publications
4
64
1
Order By: Relevance
“…Notably, a previous study also suggested improvement of the tumor uptake by combinatory treatment, whereby co-administration of the neutral endopeptidase inhibitor phosphoramidon (PA) increased the level of circulating radiopeptides, including the gastrin analogue [ 111 In]In-DOTA-MG11, and remarkably enhanced tumor uptake in mouse models 54 . In contrast to our method, this combinatory strategy robustly increased uptake in the stomach, a dose-limiting organ for PRRT with radiolabeled minigastrin 22 , and did not affect tumor viability or radio-sensitivity, which additionally can increase therapeutic responses. In addition, mTORC1 inhibition can normalize tumor vessels and enhance delivery of chemotherapeutics such as paclitaxel as previously demonstrated in rapamycin-treated breast cancer mouse models 55 .…”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…Notably, a previous study also suggested improvement of the tumor uptake by combinatory treatment, whereby co-administration of the neutral endopeptidase inhibitor phosphoramidon (PA) increased the level of circulating radiopeptides, including the gastrin analogue [ 111 In]In-DOTA-MG11, and remarkably enhanced tumor uptake in mouse models 54 . In contrast to our method, this combinatory strategy robustly increased uptake in the stomach, a dose-limiting organ for PRRT with radiolabeled minigastrin 22 , and did not affect tumor viability or radio-sensitivity, which additionally can increase therapeutic responses. In addition, mTORC1 inhibition can normalize tumor vessels and enhance delivery of chemotherapeutics such as paclitaxel as previously demonstrated in rapamycin-treated breast cancer mouse models 55 .…”
Section: Discussionmentioning
confidence: 66%
“…Furthermore, comparative biodistribution analysis in the mouse model shows that [ 177 Lu]Lu-PP-F11N reached a tumor uptake that other Lu-117-labeled mingastrin analogues could only achieve in combination with protease inhibitors indicating its high metabolic stability 21 . A more recent clinical study shows favorable biodistribution and pharmacokinetics of 177 Lu[Lu]-PP-F11N and low kidney radiation doses with a median tumor-to-kidney dose ratio of 11.6 22 . Nevertheless, in the latter study, radiolabeled minigastrin also accumulated in the stomach due to endogenous expression of the CCKBR and reached a tumor-to-stomach dose ratio of 3.34.…”
Section: Introductionmentioning
confidence: 99%
“…The additional substitution with Pro did, however, not show a considerable effect on in vivo stability. Still, the in vivo stability of [ 177 Lu]Lu- 1 is highly improved when compared to other MG analogs which are currently investigated in clinical trials [ 22 , 24 ]. For PP-F11 labeled with indium-111, the metabolic stability in the blood of mice was tested for the time point of 5 min p.i.…”
Section: Discussionmentioning
confidence: 99%
“…Most of these developments have not led to the required improvements necessary for successful clinical application. Two MG analogs, DOTA-(DGlu) 6 -Ala-Tyr-Gly-Trp-Met-Asp-Phe-NH 2 (PP-F11) labeled with indium-111 as well as DOTA-(DGlu) 6 -Ala-Tyr-Gly-Trp-Nle-Asp-Phe-NH 2 (PP-F11N) labeled with lutetium-177, which are derived from MG0 by inversion of the configuration of the penta-Glu motif, are currently examined in clinical studies ( Identifier: NCT03246659 and NCT02088645) [ 22 , 23 , 24 ]. Besides chemical modification of the peptide, in situ stabilization by co-injection of enzyme inhibitors was investigated.…”
Section: Introductionmentioning
confidence: 99%
“…PTC and follicular thyroid cancer (FTC) are classified as differentiated TCs that both arise from thyroid follicular cells and generally have excellent prognoses, while the poorly differentiated thyroid cancers have a poorer prognosis which probably arises from either PTCs or FTCs. Medullary thyroid cancer (MTC) has been derived from the parafollicular C cells, accounting for about 1-2% of TCs (5). Anaplastic thyroid cancer (ATC) originates from follicular cells and is an aggressive, undifferentiated, and rapidly fatal tumor (6).…”
Section: Introductionmentioning
confidence: 99%